2023
DOI: 10.3389/fphar.2023.1120616
|View full text |Cite
|
Sign up to set email alerts
|

Potential of natural flavonols and flavanones in the treatment of ulcerative colitis

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease generally characterized by chronic, persistent, recurrent, and non-specific ulcers of the intestine. Its main clinical manifestations include abdominal pain, diarrhea, and bloody stools. This disease is difficult to cure and even carries the risk of canceration. It has been listed as a modern refractory disease by the World Health Organization. Though a large amount of drugs are available for the inhibition of UC, the conventional treatment such as amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
0
3
0
Order By: Relevance
“…Numerous studies have demonstrated that oxidative stress can cause apoptosis through both mitochondria-dependent and mitochondria-independent pathways . Improving UC by inhibiting apoptosis through regulating oxidative stress-related signaling pathways has been widely recognized (Li et al, 2023). In response to the above studies, we found several compounds that demonstrate effectiveness in modulating this pathway.…”
Section: Compounds Targeting Oxidative Stress Induced Apoptoticmentioning
confidence: 80%
See 1 more Smart Citation
“…Numerous studies have demonstrated that oxidative stress can cause apoptosis through both mitochondria-dependent and mitochondria-independent pathways . Improving UC by inhibiting apoptosis through regulating oxidative stress-related signaling pathways has been widely recognized (Li et al, 2023). In response to the above studies, we found several compounds that demonstrate effectiveness in modulating this pathway.…”
Section: Compounds Targeting Oxidative Stress Induced Apoptoticmentioning
confidence: 80%
“…ELISA showed a significant decrease in IL-1β, IL-6, IL-8, and Fe2+, and the biochemical assay detected upregulation of SOD, GSH, and GPX4 content, and MDA expression was suppressed. Mechanistic studies showed that codonopsis extract could regulate the Keap1/ Nrf2 signaling pathway to inhibit ferroptosis (Li et al, 2023;Fang et al, 2023). These experimental results mean that modulating Nrf2 can be used as a natural target for natural products to treat UC.…”
Section: Compounds Related To Nrf2 Signaling Pathwaymentioning
confidence: 99%
“…Considering the major roles of intestinal mucosal barrier function and microflora in UC occurrence and development receive serious attentions recently, plenty of studies naturally put forward the theoretical hypothesis that restoring their functions contribute to UC prevention and treatment [6][7]. The epithelial barrier of the intestinal tract, the first defense barrier against the hostile pathogens or harmful antigens, is structurally formed by tight junctions, adheren junctions, and desmosomes between the epithelial cells [8][9].…”
Section: Introductionmentioning
confidence: 99%